A Non-uniform Stepping Mechanism for E. coli UvrD Monomer Translocation along Single Stranded DNA - Tomko, Eric J. (2007)
E. coli UvrD is an SF1 helicase involved in several DNA metabolic processes. Although a UvrD dimer is needed for helicase activity, a monomer can translocate with 3′ to 5′ directionality along single stranded DNA and this ATP-dependent translocation is likely involved in RecA displacement. In order to understand how the monomeric translocase functions, we have combined fluorescence stopped-flow kinetic methods with novel analysis methods to determine the kinetic mechanism, including ATP coupling stoichiometry, for UvrD monomer translocation along ssDNA. Our results suggest that the macroscopic rate of UvrD monomer translocation is not limited by each ATPase cycle, but rather by a slow step (pause) in each translocation cycle that occurs after four to five rapid one nucleotide translocation steps, with each rapid step coupled to hydrolysis of one ATP. These results suggest a non-uniform stepping mechanism that differs from either a Brownian motor or previous structure based inch-worm mechanisms.